COMPARISON OF DICKENSIAN CONCEPTS OF CHILDHOOD AND CONCEPTS OF CHILDHOOD IN THE WORKS OF DOSTOEVSKY (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
In this article the comparison of Dickensian concepts of childhood and concepts of childhood in the works of Dostoevsky